Mangrove ecotourism development at Karimunjawa National Park, Indonesia - PUTERI RAYSA AZZAHRA; ELHAM SUMARGA; ARNI SHOLIHAH (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Azzahra PR, Sumarga E, Sholihah A. 2023. Mangrove ecotourism development at Karimunjawa National Park, Indonesia. Biodiversitas 24: 4457-4468. Karimunjawa National Park (KJNP) is a marine conservation area with a high potential for developing mangrove ecotourism in Indonesia. Several essential aspects should be adequately understood to support mangrove ecotourism in KJNP, including the potential of tourism attractions, the ecological carrying capacity for tourism, the potential support from stakeholders, and the best strategies based on the latest conditions. This study aimed to (i) identify and analyze the potential of mangrove ecotourism attractions in KJNP, (ii) analyze the carrying capacity for mangrove ecotourism, (iii) analyze the level of influence and interest of stakeholders, and (iv) determine strategies for developing mangrove ecotourism in KJNP. The ecotourism attraction potentials were analyzed using a modified version of the assessment of Natural Tourism Attraction Objects (NTAO) (Objek Daya Tarik Wisata Alam – ODTWA). The carrying capacity was analyzed using the Area Carrying Capacity concept. The influence and interest level of stakeholders were analyzed using the economic characteristics of the community and the stakeholder grids. The strategy for developing mangrove ecotourism was determined using Strength, Weakness, Opportunity, Threat (SWOT), and Quantitative Strategic Planning Matrix (QSPM) analyses. The results showed that mangrove ecotourism in KJNP is highly potential and feasible to be developed based on the assessment of 15 criteria of NTAO with a carrying capacity of ca. 104 visitors/day. About 96% of the community agrees to support the development of mangrove ecotourism in KJNP. Karimunjawa National Park Office and the local community were identified as essential players from the eight recognizable stakeholders. Seven main strategies were formulated for developing mangrove ecotourism in KJNP, with the improvement of cooperation among stakeholders in developing facilities and tourist attractions and promoting mangrove ecotourism was perceived as the most urgent strategy to be implemented.